2004
DOI: 10.1074/jbc.m404746200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of Oversulfated Chondroitin Sulfate/Dermatan Sulfate Hybrid Chains from the Notochord of Hagfish

Abstract: Pivotal functions of glycosaminoglycan (GAG) 1 side chains of proteoglycans (PGs), especially heparan sulfate (HS), have been implicated in biological processes such as cell adhesion, proliferation, and differentiation and tissue morphogenesis (1). Chondroitin sulfate (CS) and dermatan sulfate (DS) are also found ubiquitously in the extracellular matrices and at cell surfaces, being main components of cartilage and skin, respectively. CS consists of repeating disaccharide units of -4Gl-cUA␤1-3GalNAc␤1-, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 56 publications
3
102
1
Order By: Relevance
“…Of the 678 articles that stated which Biacore platform was used, most utilized 2000 and 3000 platforms [222, (33%) and 249 (37%), respectively]. Investigators also reported data obtained from Biacore X (129, 19%) and 1000 (57, 8%), as well as from S51 [273,818,831,843,865], J [223,285,737,745,759], Q [892,905,907,910,913], Bialite [492,726,787,873] and Probe [348] platforms.…”
Section: Instrumentsmentioning
confidence: 94%
“…Of the 678 articles that stated which Biacore platform was used, most utilized 2000 and 3000 platforms [222, (33%) and 249 (37%), respectively]. Investigators also reported data obtained from Biacore X (129, 19%) and 1000 (57, 8%), as well as from S51 [273,818,831,843,865], J [223,285,737,745,759], Q [892,905,907,910,913], Bialite [492,726,787,873] and Probe [348] platforms.…”
Section: Instrumentsmentioning
confidence: 94%
“…During chain elongation in the biosynthesis of CS/DS, the disaccharide units are modified by specific sulfotransferases at C-2 of GlcA/IdoA, and C-4 and/or C-6 of GalNAc in various combinations, and display enormous structural diversity producing characteristic sulfation patterns critical 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 4 as a dramatic increase in the proportion of IdoA(2-O-sulfate)-GalNAc(4-O-sulfate) units in the cerebellum [9]. The proportion of oversulfated disaccharides and the presence of IdoA are crucial factors for the neurite outgrowth-promoting (NOP) activity of CS/DS [10][11][12][13][14]. CS/DS chains from embryonic pig brains contain a higher proportion of IdoA than those prepared from adult pig brains [12].…”
Section: Introductionmentioning
confidence: 99%
“…The average molecular size of ray cartilage CS and shark cartilage CS-C was determined to be 142 and 123 kDa, respectively, larger than that of the CS chains from other sources including embryonic pig brain (40 kDa) [10], shark skin (70 kDa) [11], shark liver (76 kDa) [15], and hagfish notochord (18 kDa) [12]. Although the two had similar structural features, the ray cartilage CS displayed higher NOP activity than shark cartilage CS-C, suggesting that the CS chains from ray cartilage contain a specific saccharide sequence required for interaction with growth/neurotrophic factors.…”
Section: Glcua(2-o-sulfate)-galnac(6-o-sulfate) (7%)mentioning
confidence: 99%
“…Several studies have shown that the sulfation pattern of CS in the brain alters during development, characterized by an increase in 4-O-sulfation and a decrease in 6-O-sulfation [5,6]. The proportion of oversulfated disaccharide units, GlcUA(2-O-sulfate)-GalNAc(6-O-sulfate) and GlcUA-GalNAc(4,6-O-disulfate), has been demonstrated to be crucial to the neurite outgrowth-promoting (NOP) activity of CS [7][8][9][10][11][12][13]. The NOP activity toward embryonic mouse hippocampal neurons of mouse brain CS/DS and shark cartilage CS/DS, which contains a high proportion of the GlcUA(2-O-sulfate)-GalNAc(6-O-sulfate) unit [13], has been verified to be executed by capturing endogenous growth/neurotrophic factors produced by non-neuronal cells (glial cells), and then presenting them to neuronal cells [4,14,15].…”
Section: Introductionmentioning
confidence: 99%